Mathematics
efreyg1brandongang
2021-05-04 18:12:51
ln (−3x − 1) − ln 7 = 2 ln (4x + 1) − ln 3 = 5
ANSWERS
richard260403
2021-05-05 00:12:45

[latex]D: -3x - 1 extgreater 0 \ \ -3x extgreater 1 \ \ x extless - frac{1}{3} [/latex] [latex]ln (-3x-1) - ln 7 = 2 \ \ ln ( frac{-3x-1}{7}) = 2 \ \ ln ( frac{-3x-1}{7}) = ln e^{2} \ \ frac{-3x-1}{7} = e^{2} \ \ -3x - 1 = 7e^{2} \ \ 7e^{2} +1 = -3x \ \ oxed{x = frac{-7e^{2}-1}{3} } [/latex] [latex]D: \ \ 4x+1 extgreater 0 \ \ 4x extgreater - 1 \ \ x extgreater - frac{1}{4} [/latex] [latex]ln(4x+1) - ln 3 = 5 \ \ ln ( frac{4x+1}{3}) = 5 \ \ ln ( frac{4x+1}{3}) = ln e^{5} \ \ frac{4x+1}{3} = e^{5} \ \ 4x+1 = 3e^{5} \ \ 4x = 3e^{5} - 1 \ \ oxed{x = frac{3e^{5}-1}{4} }[/latex]

ADD ANSWER